Association of direct bilirubin to total bilirubin ratio with 90-day mortality in patients with acute-on-chronic liver failure - Ma, Yuanji; Du, Lingyao; Zhou, Shaoqun; Bai, Lang; Tang, Hong (Frontiers in Medicine, 2023)
Background: Hyperbilirubinemia occurs when the liver fails to process bilirubin properly. A disproportionate increase in direct bilirubin indicates a decreased ability of the hepatocytes to uptake and/or convert bilirubin, which may impact the prognosis of patients with acute-on-chronic liver failure (ACLF). However, the association of direct bilirubin to total bilirubin ratio (DB/TB) with outcomes in patients with ACLF remains unclear.Methods: A retrospective study was conducted in West China Hospital of Sichuan University to assess the association between DB/TB and 90-day mortality in patients with ACLF. The diagnosis of ACLF was based on the Chinese Group on the Study of Severe Hepatitis B (COSSH) ACLF criteria. Ordinal logistic regression models, linear regression models, and Cox proportional hazards models were applied to evaluate the association between DB/TB and hepatic encephalopathy, disease severity, and outcome, respectively.Results: A total of 258 patients with ACLF were included. The surviving patients were less likely to have liver cirrhosis and comorbidities, and their disease severities were milder than the dead. DB/TB was negatively correlated to cerebral score for hepatic encephalopathy (adjusted odds ratio: 0.01, p=0.043), and disease severity (adjusted standardized coefficients: -0.42~-0.31, all p<0.001), respectively. A significant 90-day mortality risk of DB/TB was observed (all adjusted hazard ratio (aHR) <0.20 and all p≤0.001). Compared with patients with DB/TB <0.80, patients with ACLF and DB/TB ≥0.80 had much lower 90-day mortality risk (all aHR <0.75 and all p<0.01).Conclusions: DB/TB could be an independent risk factor to predict the short-term prognosis in patients with ACLF. More attention should be paid to patients with lower patients 删除[Author]: